A benchmark study on the flow metering systems for the characterisation of fuel injectors for future heavy duty commercial vehicles. (1st March 2020) - Hogg, Thomas; Stojanovic, Stefan; Tebbs, Andrew; Samuel, Stephen; Durodola, John
Highlights: This study aims to determine the most suitable flow metering device. The study focuses on three commercially available metering devices. An experiment was carried out to benchmark the performance of each. Abstract: This study aims to determine the most suitable flow metering device for the characterisation of heavy duty diesel injector behaviour. The study focuses on three commercially available metering devices and the main principles they employ. An experiment was carried out to benchmark the performance of each device's measurement repeatability in the characterisation of fuel injector behaviour. This study then compares the capabilities and suitability of each for use in a production environment. The comparison was carried out for Delphi Technologies using the new DFi21 heavy duty diesel injector which uses miniaturised hydraulic three way control valve technology.